(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Shrinkflation is the hone of decreasing the size or quantity of a item whereas the cost of theitem remains the same or marginally increments. It is a combination of two words shrink and inflation=Shrinkflation. In a few cases, the term may show bringing down the quality of a item or its fixings whereasthe cost remains the same. Rs. 10- Dairy Milk was premium to eat and they have been also selling Rs. 5-but now Rs. 5- is Rs. 10- andwith much smaller size and infact they are the most shrinking size dealingcompany. I hope they will at leastallow one tooth to eat Rs. 10- chocolate. Same is the case of Choco Bar,Rs. 5- size became Rs. 10- and Rs.10- became Rs. 20-.